The Implementation of Herringbone Technique to Improve Students’ Reading Comprehension - Nur Halimah; Fadhlan Saini; Indah Wardaty Saud; Nur Mutmainnah (ELITE JOURNAL, 2023)
The objectives of the research are: (1) To find out whether the Herringbone technique able to improve students’ reading comprehension. (2) To describe what extent does the implementation of Herringbone technique to improve students’ reading comprehension. The researchers applied classroom action research (CAR) as the design of this study. The subjects were 19 students of class XI MIA II MAN 1 Bitung which consisted of 8 male students and 11 female students. In this research, the researchers used several data collection instruments, including observation, interview, tests, and documentation. Having given the test, the researchers instructed the research subjects to work on multiple-choice questions. This research involved two cycles: such as cycle I and cycle II. During the cycles, there were four stages included, namely: planning, action, observation, and reflection. The findings said that the achievement of the students' completeness percentage in pre-test was low (31.58%). It can be stated also that the attention and the participation of students was not effective enough. Meanwhile, the result of cycle I showed that the percentage of students’ completeness was 47.37%. From this result, there seemed to have more cycle to solve. Likewise, the researchers carried out the second cycle to revise problems in the first cycle. For the result of cycle II, it showed that herringbone technique improved students' reading comprehension skills. It was supported by seeing the students active in responding the material like asking question, having enthusiasm to do the exercise, participating in discussions, and improving themselves in every test. This was also proven by the increase in the percentage of students' completeness in the cycle II (84.21%). Key Words: Herringbone Technique, Reading Comprehension